Social Media Influencers Marketing Strategy in Increasing Marketing Impact - Popo Suryana (SEAN Institute, 2023)
The phenomenon of using social media influencers as marketing agents has become an integral part of business strategy in the digital era. This research will focus on how influencers utilize social media platforms to increase their influence in reaching audiences, building brand images, and ultimately increasing marketing impact. This research aims to investigate and analyze the marketing strategies used by social media influencers and their impact on the effectiveness of product or service marketing. This research uses a qualitative approach with descriptive methods. The results of this research show that marketing strategies through social media influencers have a positive impact in increasing brand awareness, consumer engagement and company image. Selection of influencers that align with brand values, long-term collaboration, creative content, and active participation in the community have proven to be key factors in achieving campaign success. Choosing the right social media platform also plays a significant role in reaching a diverse audience. Regularly measuring performance using KPIs is an important step in evaluating campaign effectiveness and making necessary adjustments. In conclusion, marketing through social media influencers is not just a promotional tool, but also a strategic approach that is able to build strong relationships, increase engagement, and strengthen brand image in this digital era.